Impacto de produtos fitossanitários sobre aspectos biológicos do ácaro predador Neoseiulus barkeri Hughes (Acari: Phytoseiidae) - Matos, Mateus de Castro (2023)
Multiple pest arthropods can occur in cultivated botanical species and directly impact agricultural production. The management of pest arthropods is an arduous task and the adoption of control measures for one species can impact other species in the community and lead to the emergence of secondary pests. So it is expected that different strategies are employed within a crop management plan to minimize agricultural losses. The chemical control is the most used method, but it has risks associated with human health and the environment and its application has been used with greater caution and with a reduction in the frequency of use. In this scenario, other strategies received more attention, especially biological control. Despite the various strategies for using natural enemies, biological control as an exclusive method of control is limited, being possible only when the target pest is kept below the level of economic damage without other interventions. The integration of control methods becomes essential, but sometimes some strategies become incompatible, mainly between chemical and biological control. This happens because of the lethal and sublethal potential of pesticides on natural enemies. The study of the pesticide-natural enemy interaction is necessary for the selection of selective products or those that cause minimal impact on natural enemy populations, enabling the integration of chemical and biological control. An important biological control agent is the predatory mite Neoseiulus barkeri Hughes (Acari: Phytoseiidae), a generalist mite, commercially available and effective for the management of several species of pest arthropods in different cultures. Knowing the predatory potential of the predatory mite N. barkeri, the focus is on the use of less toxic selective pesticides for this predator. Therefore, studies that observe the effects of pesticides on N. barkeri contribute directly to the enrichment of knowledge about the use of this predatory mite and may even suggest one or more products suitable for integrated use.